2007
DOI: 10.1007/s00540-006-0469-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing intraoperative bradycardia in adult patients

Abstract: The most prominent factor affecting heart rate was atropine premedication. It was noteworthy that a single preoperative administration of atropine affected heart rate throughout the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…Our criteria used for bradycardia are consistent with previously published papers. 8,17,18 A sensitivity analysis was also conducted by excluding patients with a preoperative hypotension (systolic blood pressure <110 mmHg) and preoperative bradycardia (HR <60 beats per minute). Patients were followed throughout their hospitalization for the secondary composite end-point of any cardiovascular event including development of any of heart failure, acute coronary syndrome, stroke, transient ischemic attack, arrhythmia or death.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Our criteria used for bradycardia are consistent with previously published papers. 8,17,18 A sensitivity analysis was also conducted by excluding patients with a preoperative hypotension (systolic blood pressure <110 mmHg) and preoperative bradycardia (HR <60 beats per minute). Patients were followed throughout their hospitalization for the secondary composite end-point of any cardiovascular event including development of any of heart failure, acute coronary syndrome, stroke, transient ischemic attack, arrhythmia or death.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…2,7 However, there are no currently existing tools to predict which patients are at risk for intraoperative hemodynamic instability and few studies evaluating risk factors for development of intraoperative bradycardia. [8][9][10] Understanding a patient's risk for intraoperative hemodynamic instability in the preoperative setting may help guide management of preoperative medications or anaesthetic agents.…”
mentioning
confidence: 99%
“…Yorozu et al [14] reported a retrospective examination showing factors that influence intraoperative bradycardia in adult patients. They revealed that the most prominent factor to affect heart rate was premedication with atropine.…”
Section: Discussionmentioning
confidence: 99%
“…Doyle DJ reported that refl ex bradycardia and sinus arrest may occur in any sort of surgical procedures, neurosurgery to intraabdominal, ophthalmic and simple liver biopsies as well and premedication with an anticholinergic agent may be a suitable preventive measure 6 . Yorozu I et al reported that common causes of bradycardia during general anaesthesia are drugs like Propofol, Vecuronium, newer synthetic opioids, pneumoperitoneum creation and vagal stimulation and Atropine premedication keeps the heart rate in high normal side in whole perioperative period 1 . In present study also Atropine administered patients had heart rate of 105.89 (8.82) per minute and there was no evidence of bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Initially used drugs like Pethidine, Sodium thiopentone and Pancuronium were vagolytic and there was no bradycardia and hypotension following use of these drugs. The newer drugs like Fentanyl, Propofol and Vecuronium which are being used extensively during general anaesthesia are vagotonic and can cause severe bradycardia and even asystole during carboperitoneum creation for laparoscopic surgery 1,2 .…”
mentioning
confidence: 99%